First aid manual : the authorised manual of St. John Ambulance, St. Andrew's First Aid and the British Red Cross - St. John Ambulance (England),|eissuing body.; St. Andrew's First Aid,|eissuing body.; British Red Cross Society,|eissuing body. (London : Dorling Kindersley, 2016)
The First Aid Manual covers all aspects of first aid, from emergency first aid and first aid for babies and children to resuscitation. Find out how to treat over 100 different conditions, from splinters and sprained ankles to strokes and unconsciousness and how to use essential equipment
Previous edition: 2011.
Includes index.
Keywords: First aid in illness and injury -- Handbooks, manuals, etc; Wounds and injuries -- Treatment